Konsep Simbolisasi Dan Identitas Politik Sebagai Bentuk Propaganda Di Indonesia - Prasetya, Arif Budi (Tuturlogi: Journal of Southeast Asian Communication, 2023)
Politics and identity are closely related to the practice of power in a particular area. In the 2019 election phenomenon in Indonesia, the concept of symbols and identities of parties and election participants were scattered, both directly and in the media frame. The construction of party identity symbols and figures carried by election participants consists of parties and individuals, for example the PDI-Perjuangan, Democrats and Gerindra. While the symbolic figures are Jokowi, Susilo Bambang Yudhoyono, Prabowo, and Sandiaga Uno. By looking at the level of power relations and the relationship between political symbols, it can be identified the concept of political propaganda through these symbols in order to gain power, or lay the foundation of certain ideologies.